A descriptive study of lead arm muscle activation patterns during cricket batting - McCarthy, Ryan Aidan (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Introduction: Kinematic studies identify elbow extension and wrist flexion as key movements for bat swinging speed during cricket batting. Knowledge of lead arm muscle activation during cricket batting may provide a greater understanding of the mechanics leading to the generation of faster bat speed. Aim: The current investigation aimed to determine selected muscle activation of cricketer's lead arm, maximum bat swinging speed and angular separation of the pelvis and thorax in the transverse plane (known as the X-angle) during a distance-hitting batting protocol. Materials and Methods: 12 cricket players playing for a South African school 1st XI school team aged 16-19 years completed a distance-hitting batting protocol. Due to issues in data recording two participants' data was excluded leading to 10 participants being kept in the final analyses.Participants attempted to hit straight lofted drives while facing full-length deliveries at 80-100 km.h-1 from a bowling machine. Each participant faced 12-24 balls split into overs while lead arm muscle activation, bat speed, and angle of lead-elbow flexion were recorded. Each participant's elbow and wrist flexors and extensors were monitored by electromyography (EMG) units while they batted. The EMG units were placed on the wrist flexor and extensor origins and on Triceps and Biceps Brachii. Muscle activation for each muscle was recorded in millivolts (mv) and divided by the maximum measurement of voluntary muscle activation to determine the percentage of maximum voluntary contraction (%MVC) during each shot. Percentage MVC for batting phases of backlift, downswing, contact and follow-through were averaged to compare average %MVC per muscle across all batters and obtain inter-participant variability. Lead arm elbow angle and the %MVC of the elbow and wrist muscles will be compared between successful and unsuccessful shots for analysis. Each participant's lead arm elbow angle was monitored in degrees of flexion by a goniometer placed across the anterior aspect of the elbow joint. Due to the data not having a normal distribution, non-parametric tests were used to establish the variance between dependent variables. To determine the effect of multiple groups on the independent variables a Kruskal-Wallis test for ANOVA was used. Where significant differences were identified, multiple pairwise comparisons were completed to determine where the differences occurred. Results: Successful Lofted straight drives (32 shots) were compared to unsuccessful shots (101 shots) across all participants. Participants and batting phase were found to be significantly different for lead arm elbow angle and muscle activation however shot type was not found to be significantly different. Meaning that lead arm elbow angle and muscle activation differ based on the participant observed or based on the batting phase observed. The backswing phase recorded a higher amount of elbow flexion (155.25°) for Lofted straight drive compared to unsuccessful shots (157.86°) and lower activation across all muscles for Lofted straight drive. The lofted straight drive had a higher amount of elbow flexion (129.52°) compared to unsuccessful shots (149.24°) for the downswing phase and muscle activation was similar with greater variation for unsuccessful shots. At contact Lofted straight drive had a higher amount of elbow flexion (153.44° v 160.13°), and higher activation in the Biceps brachii (34.61% v 28.41%) and Triceps brachii (51.07% v 43.02%). For the follow-through phase Lofted straight drives had a higher amount of elbow flexion (144.87° v 149.59°) and greater Forearm extensor activation (37.13% v 31.28%). There was a large variation across all phases (coefitient of variation between 8.79%-70.28%) with backswing having the least variation and contact having the greatest. Meaning that the backswing phase is fairly predictable for batters and the contact phase is highly variable. Conclusion: Muscle activation increased in the last few milliseconds before contact. The Forearm extensor had the greatest activation during the backswing and follow-through phases. During the downswing phase, Forearm flexors had the greatest activation and at contact, the Triceps brachii had the greatest activation. This study emphasizes the importance of forearm and elbow muscle for batting. Appropriate strengthening of the muscles could also help a batter execute a powerful lofted drive. Future studies with objective measures linked to batting success in prior studies can build on the importance of these findings for batter success. This study provides insight into individual batter techniques and identifies important topics for future research.
Keywords: Cricket -- Batting; Muscle contraction; Elbow; Wrist; Forearm; Cricket players; School sports